Kierkegaard's Concept of Anxiety (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study aim first at examining the concept of anxiety as expressed by the existential philosopher Kierkegaard in his various philosophical works. It aims also at tracking the developmental context of this concept which comprises three essential stages: the aesthetic stage, the moral stage, and the religious stage. The concept of anxiety was represented in a way that was in line with the features of each of these three stages.Further, this study tries to find out the justifications that led Kierkegaard to make this concept of anxiety more developed and more capable of further development in the religious stage where the individual finds herself facing a large number of possibilities and options in her attempt to achieve her freedom in existence and, therefore, live true faith, which in its turn cannot be assimilated into the self without feeling the productive positive anxiety which is part of the nature of existence itself.